PENGARUH PENGGUNAAN SPONTAN POWER TERHADAP UNJUK KERJA MOTOR BENSIN NF 100 D - -, Sudarsono (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Vehicles that are mostly still using conventional fuels (gasoline and diesel). The fuel demand is increasing in many areas, especially for automotive so we need to save energy by increasing engine performance. This case forced to examine the effect of using and without out the spontan power to the engine performance. This study used the constant load for each test (standard engine and the spontan power) with the variation of rotation 1500, 2000, 2500, 3000, 3500 , 4000, 4500, 5000, 5500, 6000 and 6500 rpm in laboratorium. This research was also conducted in the field to know the difference in ecceleration.The test had been conducted to assess the performance of a 4-stroke motor-cycle engine of 100cc Honda supra x 2001 and the result said that using the spontan power the torque rose 17.85% to standard conditions, the average power rose 14.79 % to standard conditions, the everage effective pressure rose 17.82%, average fuel consum-ption reduced 7.112% to standard condition and the everage efficiency increase 24.303% to standard condition.